Unmasking Hepatitis A: A Case Study of Atypical Presentation in a Returning Traveler From Egypt - Emmanuel Edwar Siddig; Claude M. Muvunyi; Ayman Ahmed (Case Reports in Hepatology)
Hepatitis, characterized by inflammation of the liver, arises from various infectious and noninfectious causes, with viral hepatitis being caused by a diverse group of viruses including hepatitis A, B, C, D, and E. Infection with the Hepatitis A virus (HAV) can result in liver inflammation and damage, primarily spread through fecal–oral contamination. Clinical symptoms often overlap with other infections, complicating diagnosis in returning travelers from endemic regions. This case study focuses on a 46-year-old Sudanese housewife who presented with symptoms of fever, chills, headache, and muscle aches, along with a high temperature of 103.5°F, following a recent visit to Egypt. The initial assessment showed hemodynamic stability and abnormal liver function tests. This raise suspicion about the potential involvement of several infections including malaria, hepatitis, arboviral diseases such as Chikungunya, Yellow, and dengue fevers. Further investigations revealed acute hepatitis A infection confirmed through positive serology. Notably, the patient displayed atypical features such as atypical lymphocytosis, splenomegaly, and mild anemia. This case emphasizes the significance of essentially considering a wide range of diseases among travelers including hepatitis A among people coming from highly endemic areas such as Egypt, even when the patient is not manifested with the typical clinical presentation of specific disease. Particular attention is needed for epidemic-prone infections like hepatitis A.